Strategies for the Synthesis of Fluorinated Nucleosides, Nucleotides and Oligonucleotides. Issue 9 (31st May 2022) - Shet, Harshita; Sahu, Rajesh; Sanghvi, Yogesh S.; Kapdi, Anant R.
Abstract: Fluorinated nucleosides and oligonucleotides are of specific interest as probes for studying nucleic acids interaction, structures, biological transformations, and its biomedical applications. Among various modifications of oligonucleotides, fluorination of preformed nucleoside and/or nucleotides have recently gained attention owing to the unique properties of fluorine atoms imparting medicinal properties with respect to the small size, electronegativity, lipophilicity, and ability for stereochemical control. This review deals with synthetic protocols for selective fluorination either at sugar or base moiety in a preformed nucleosides, nucleotides and nucleic acids using specific fluorinating reagents. Abstract : Since the 1950s, medicinal chemists and chemical biologists have been interested in chemically modified fluorinated nucleosides and oligonucleotide derivatives owing to the unique properties of fluorine atom and their potential as anticancer, antibacterial, and antiviral drugs. In this review, we have summarized the synthetic protocols for selective fluorination either at sugar or base moiety in a preformed nucleosides, nucleotides and nucleic acids using specific fluorinating reagents.